Analysis of Cognitive Therapy on Increased Self-Esteem and Elderly Happiness in the Elderly Cottage of the Al-Ishlal Foundation Malang - Asep Dwi Prayetno; Byba Melda Suhita (Journal for Quality in Public Health, 2022)
Elderly is said to be the final stage of development in the human life cycle including biological, psychological and social, these changes will automatically affect the lives of the elderly, especially regarding the problems of self-esteem and happiness of the elderly. The purpose of this study was to analysis of cognitive therapy on increased self-esteem and elderly happiness in the elderly cottage of the Al-Ishlah foundation Malang. The design of this research is Quasy-Experimental with Time Series Design method. The population is elderly with impaired self-esteem and happiness. The sample was selected using a purposive sampling technique with inclusion and exclusion criteria and obtained a sample of 20 people. The variables measured in this study were self-esteem and happiness. The statistical test used was the Wilcoxon test with a 95% confidence level. The results of the pretest measurement showed that most of the respondents experienced low self-esteem 12 (60%) and moderate happiness 13 respondents (65%), and the posttest measurement results showed that almost all respondents had high self-esteem and high happiness 18 respondents (90%). The results of statistical analysis showed that there was a significant increase in self-esteem and happiness with a total value of p = 0.001. Seeing the results of this study, cognitive therapy which aims to change negative thoughts into positive thoughts, which is proven to increase self-esteem and happiness, the working system is that negative thoughts are rationalized and converted into rational positive thoughts by carrying out positive behaviors or activities and socialize with individuals around and the environment. With lots of positive activities will eliminate negative thoughts.